2000
DOI: 10.1108/00070700010310614
|View full text |Cite
|
Sign up to set email alerts
|

Situational determinants of fish consumption

Abstract: Despite having properties well-suited to``healthy-eating'', fish is a declining product. Consumers' evaluations of fish are known to differ between consumers and non-consumers, but the precise differences, which might be of use in the development of a marketing campaign, are vague. Analyses suggest that the factors that influence consumer choice are predominantly environmental, and a model of situational determinants of consumption (the behavioural perspective model or BPM) is proposed as a theoretical framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 29 publications
12
113
1
4
Order By: Relevance
“…Consumers' perception of the smell of fish, fish bones, and fish price is not as positive as their perception of its health benefits (Verbeke & Vackier, 2005). Leek et al (2000) stated that fish bones are one of the most important factors reducing consumption frequency, and they added that fish bones cause problems in cooking and preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Consumers' perception of the smell of fish, fish bones, and fish price is not as positive as their perception of its health benefits (Verbeke & Vackier, 2005). Leek et al (2000) stated that fish bones are one of the most important factors reducing consumption frequency, and they added that fish bones cause problems in cooking and preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatives such as farmed fish may need to become a greater food source for delivery of n-3 LCPUFA. Therefore the challenge is to encourage non-fish eaters to include fish and seafood in their habitual diets, and to overcome reported barriers to intake, including undesirable physical properties (smell and bones), difficulties with preparation and cooking, unaffordability, presence of food allergies, and a perceived risk of pollutants [38,[50][51][52]. Communication of health messages that encourage children to include more fish in their diet [53,54] will be one aspect, while educating parents and caregivers about practical, easy ways to prepare fish dishes may be of higher importance.…”
Section: Discussionmentioning
confidence: 99%
“…While Leek et al [14] Honkanen et al [15] Olsen [16] reported that price, value for money and household income were not perceived as a barrier for insurance consumption [17] found that high price had a negative impact on attitude toward consumption. Financial literacy is strongly and positively related to attitudes towards insurance consumption [18].…”
Section: People Attitude Towards the Life Insurancementioning
confidence: 99%